Review: Dunmore, Stuart S. 2019. Language Revitalisation in Gaelic Scotland: Linguistic Practice and Ideology - Hornsby, Michael (Studia Celtica Posnaniensia, 2019)
Review: Dunmore, Stuart S. 2019. Language Revitalisation in Gaelic Scotland: Linguistic Practice and Ideology. Edinburgh: Edinburgh University Press. 224 pages. ISBN: 978-1-474443111. Review by MICHAEL HORNSBY, Adam Mickiewicz University in Poznań.